Updates on the Methodological Approaches for Carrying Out an In-Depth Study of the Cardiac Conduction System and the Autonomic Nervous System of Victims of Sudden Unexplained Fetal and Infant Death - Alfonsi, Graziella; Crippa, Marina (Frontiers in Medicine, 2016)
This article contains a set of protocols for histopathological techniques that can be used for carrying out in-depth studies of cases of Sudden Infant Death Syndrome (SIDS) and Sudden Unexplained Fetal Death Syndrome (SIUDS). In order to enable researchers to advance hypotheses regarding the causes of the unexpected death of infants and fetuses, the authors propose three innovative and accurate methodologies for studying the Cardiac Conduction System, the peripheral cardiac nervous system and the central autonomic nervous system. Over the years, these protocols have been developed , modified and improved on a vast number of cases which has enabled pathologists to carry out the microscopic analyses of the structures which regulate life, in order to highlight all the possible morphological substrates of pathophysiological mechanisms that may underlie these syndromes. In memory of our research professor Lino Rossi (1923-2004).